Microplastics in Food: A Review on Analytical Methods and Challenges - Kwon, Jung-Hwan; Kim, Jin-Woo; Pham, Thanh Dat; Tarafdar, Abhrajyoti; Hong, Soonki; Chun, Sa-Ho; Lee, Sang-Hwa; Kang, Da-Young; Kim, Ju-Yang; Kim, Su-Bin; Jung, Jaehak (International journal of environmental research and public health, 2020)
Human exposure to microplastics contained in food has become a significant concern owing to the increasing accumulation of microplastics in the environment. In this paper, we summarize the presence of microplastics in food and the analytical methods used for isolation and identification of microplastics. Although a large number of studies on seafood such as fish and shellfish exist, estimating the overall human exposure to microplastics via food consumption is difficult owing to the lack of studies on other food items. Analytical methods still need to be optimized for appropriate recovery of microplastics in various food matrices, rendering a quantitative comparison of different studies challenging. In addition, microplastics could be added or removed from ingredients during processing or cooking. Thus, research on processed food is crucial to estimate the contribution of food to overall human microplastic consumption and to mitigate this exposure in the future.